2022
DOI: 10.21203/rs.3.rs-1478439/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Second Booster Vaccine and Covid-19 Mortality in Adults 60 to 100 Years Old

Abstract: The rapid emergence of the B.1.1.529 (omicron) variant of severe acute respiratory syndrome coronavirus-2 led to a global resurgence of coronavirus disease 2019 (Covid-19). Israeli authorities approved a 4th Covid-19 vaccine dose (second-booster) for individuals aged 60 and above who received a first booster dose four or more months earlier. Evidence regarding the effectiveness of a second-booster dose in reducing mortality due to Covid-19 is warranted. This retrospective cohort study included all members of C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
1
10
0
1
Order By: Relevance
“…VE against infection was modest and declined rapidly. Two other studies comparing four- to three-dose recipients, reported VE of 64-73% against severe disease at a 4-9 week follow-up [10,11], and 88% against mortality during a 10-week follow-up [14]. Our findings show another added benefit from the fourth dose.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…VE against infection was modest and declined rapidly. Two other studies comparing four- to three-dose recipients, reported VE of 64-73% against severe disease at a 4-9 week follow-up [10,11], and 88% against mortality during a 10-week follow-up [14]. Our findings show another added benefit from the fourth dose.…”
Section: Discussionsupporting
confidence: 56%
“…Vaccination against SARS-CoV-2 has resulted in a significant change in the response to COVID-19 since the end of 2021. Nevertheless, due to waning immunity [1][2][3], a third dose given as a booster became an essential countermeasure during the Delta variant wave a few months later [4,5]. The spread of the Omicron variant has challenged even the most vaccinated populations, with lower vaccine effectiveness (VE) and high rate of breakthrough infections [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A preprint of another Israeli study showed that mortality from covid-19 was 78% lower after a second booster in a group of people over 60 6…”
Section: Ongoing Studymentioning
confidence: 99%
“…1,2 Vaccine effectiveness following a primary series and single booster dose appears to wane, and observational studies suggest that a second booster dose is associated with increased protection against severe COVID-19 and death. 3,4 However, the absolute benefi t may be very small and the duration of effect is uncertain. Among those eligible for a second booster dose, we individualize the decision based on patient preference, risk for severe disease, and risk of exposure; those at the highest risk are most likely to benefi t.…”
Section: Family Medicine -Immunizationsmentioning
confidence: 99%